Lipopolysaccharides of Bacteroides intermedius (Prevotella intermedia) and Bacteroides (Porphyromonas) gingivalis induce interleukin-8 gene expression in human gingival fibroblast cultures. - Tamura, M (1992)
Lipopolysaccharides (LPS) prepared from Bacteroides intermedius (Prevotella intermedia) and Bacteroides (Porphyromonas) gingivalis by hot phenol-water extraction induced interleukin-8 (IL-8) mRNA in normal human gingival fibroblast cultures, as demonstrated by Northern (RNA) blot analysis. IL-8 mRNA levels began to increase after a 2-h exposure, reached a maximum after 12 h, and then dropped to the unstimulated level at 48 h. IL-8 mRNA levels were also enhanced in a dose-dependent manner. By contrast, LPS specimens from various Salmonella species with S and R chemotypes and bacterial [corrected] and synthetic lipid A preparations did not increase IL-8 mRNA levels in fibroblasts. Although recombinant human IL-1 alpha induced IL-8 mRNA expression in fibroblast cultures, an antiserum to recombinant human IL-1 alpha did not decrease the IL-8 mRNA accumulation induced by B. intermedius LPS. Fibroblasts primed with natural human gamma interferon (IFN-gamma) expressed higher IL-8 mRNA levels upon stimulation with B. intermedius LPS, but not with Salmonella LPS, compared with nontreated cells. Natural human IFN-beta exhibited a similar priming effect on the fibroblasts, and antiserum to IFN-beta added to the cultures together with B. intermedius LPS decreased the IL-8 mRNA levels. Therefore, endogenous IFN-beta enhanced IL-8 mRNA production in response to B. intermedius LPS in fibroblasts.